Pediatric functional dyspepsia: A comprehensive review - Liz Febo-Rodríguez (Permanyer, 2021)
Functional dyspepsia (FD) is a common but heterogeneous upper gastrointestinal disorder that causes recurrent and/or chronic epigastric symptoms, with an estimated prevalence in children between 3% and 27%. Etiologies include genetic predisposition and events that cause disruption of the brain-gut-microbiota axis, such as environmental and psychosocial stressors, disturbance of the gut microbiota, and early life events that lead to hyperalgesia such as cow's milk protein. FD results in impaired quality of life and increased health care costs, with an estimated $5 billion in annual costs. Unfortunately, treatment options are limited given the complexity of its pathophysiology and the fact that most therapies are studied in adults and not children, thus making FD difficult to manage in pediatrics.